Analisis Faktor Peningkatan Pakan Ayam Petelur PT. Japfa Comfeed Indonesia Tbk. Menggunakan Grounded Theory - Ira Ariati (Publikasi Indonesia, 2022)
One of the determining factors for the success of laying hens is the availability of feed that is suitable for livestock needs, both in terms of quantity and quality. This will also be closely correlated with the costs incurred, the more efficient the use of feed, the greater the income of farmers can be. Feed is one of the important components that determine success in laying hens cultivation. In addition to having a direct effect on production performance, feed costs are the biggest costs that must be incurred. This study uses a qualitative technique with a grounded theory approach. The author conducted direct interviews with PT Japfa Comfeed Indonesia Internal, Tbk. and from External Parties (Ministry of Animal Husbandry, Ministry of AgriculturMMe, and Ministry of Trade) to determine the impact of rising corn prices on feed prices. Results Based on the research, it was found coding scheme consisted of 21 codes that formed 14 categories and gave rise to 3 themes with a total score of 36. The biggest score in coding was 16 on the theme of increasing production operational costs so that the factor that greatly influenced the increase in the price of CAL-9 laying hens at PT Japfa Comfeed Indonesia Tbk was the increase in production operating prices.